Azolla as an Economic Substitute to Soybean Based Feed for Poultry - Paudel, Dev Raj; Dhakal, Pramila; Timsina, Kailash P.; Dahal, Ananta (International Journal of Applied Sciences and Biotechnology, 2015)
A study on azolla as an economical substitute to soybean based poultry feed was conducted. The experiment consisted of four treatments laid out in Completely Randomized Design (CRD) with five replications. Each experimental unit consisted of three birds. For this purpose, eight-day old, unsexed Hubbard broiler chicks were weighed and randomly assigned to each treatment. Four different levels of azolla meal were incorporated in the starter and finisher ration at a level of 0%, 10%, 15%, and 20% respectively. Body weight, weight gain, feed consumption, and feed efficiency were measured. The average cumulative weekly body weight for all weeks were found to be significantly different (P<0.05) for the various treatments. Maximum cumulative body weight (1360 g) was found in broiler fed T2 ration in 5th week. Similar trend was also observed in 6th week showing highest cumulative weight (1882 g) in control diet (T1) which was at par with T2 (1841 g). Significantly highest (420.3 g) live weight gain was observed in T2 diet during 5th week. Overall mean of weekly feed consumption was recorded highest (784.33 g) in T2 diet. The economic analysis of net income/kg live weight was the highest (Rs 18.86) in T1 which was at par with T2 (Rs 18.35). Likewise, cost of production/bird was highest (Rs 124.5) in T1 and lowest (Rs 112.2) in T4. The results show that azolla meal could be utilized to substitute up to 10% soybean meal from overall production and economic point of view. Int J Appl Sci Biotechnol, Vol 3(4): 619-625